If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+66=2x-14
We move all terms to the left:
6x+66-(2x-14)=0
We get rid of parentheses
6x-2x+14+66=0
We add all the numbers together, and all the variables
4x+80=0
We move all terms containing x to the left, all other terms to the right
4x=-80
x=-80/4
x=-20
| -30+y=6 | | 1/10x-3=4 | | -3=9z+8z | | -4=-7+x.5 | | x=5.5x+3x2-15+2x | | 5+c=-4 | | -5+2=9z+8z | | 1/5p+3=11 | | 4(4-3p)=52 | | -57=-3(3+4b) | | 165=10k-5 | | 56.25=x^2 | | -6x+-36=-36+4x | | 1+1.4y=1.7 | | 1/3c-9=1 | | -4n+30=10 | | 84=151x/14 | | -4(4v-3)+v=42 | | 14x=-3x+34 | | 15m+12=9m+36m | | 1/2y+10=20 | | -8x+-48=-48+36x | | 1/7x+6=8 | | 9y^2-7y=4 | | 30=5x-32=7x+12-9x | | 2+2x=-2x-(-2 | | 2x-(5x+7)=8x-7 | | h^2+(h-7)(h+7)=13^2 | | x+4x=-35 | | 4x-4=-12+12x | | 5x+9=2x+89 | | 8s-4=32 |